2023
DOI: 10.3389/fpsyg.2022.874261
|View full text |Cite
|
Sign up to set email alerts
|

The sexual selection of creativity: A nomological approach

Abstract: Cultural innovations, such as tools and other technical articles useful for survival, imply that creativity is an outcome of evolution. However, the existence of purely ornamental items obfuscates the functional value of creativity. What is the functional or adaptive value of aesthetic and intellectual ornaments? Recent evidence shows a connection between ornamental creativity, an individual’s attractiveness, and their reproductive success. However, this association is not sufficient for establishing that crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 295 publications
0
8
0
Order By: Relevance
“…According to the first interpretation, whenever people appear to make overly large investments in technological exploration, there should exist selfish or genetic returns that are worth the cost. Such returns may come in a variety of forms in the short or long term: monetary or material returns from selling or trading innovative products, an increased survival for one's own group in competition with other groups, prestige or a positive reputation in society [38,39], sexual appeals to potential reproductive mates [40][41][42][43] or indirect benefits through the success of genetically related individuals (e.g. offspring or younger siblings; [24,44]).…”
Section: Implications Of the Negative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the first interpretation, whenever people appear to make overly large investments in technological exploration, there should exist selfish or genetic returns that are worth the cost. Such returns may come in a variety of forms in the short or long term: monetary or material returns from selling or trading innovative products, an increased survival for one's own group in competition with other groups, prestige or a positive reputation in society [38,39], sexual appeals to potential reproductive mates [40][41][42][43] or indirect benefits through the success of genetically related individuals (e.g. offspring or younger siblings; [24,44]).…”
Section: Implications Of the Negative Resultsmentioning
confidence: 99%
“…food or mating opportunities) for experts' valuable knowledge or its products [39]. The benefit through increased sexual appeal [40][41][42][43] can be even more challenging to model because it involves sexual selection; that is, we need to work on an explicit two-sex model in which time-allocation strategies and cumulative technology evolve on one sex and mate choice preference on the other, although it is also possible that technology is transmitted bilaterally and both sexes evaluate the competency of each other.…”
Section: Implications For Evolutionary Dynamicsmentioning
confidence: 99%
“…Although short-term mating behavior is most relevant for the theory of sexual selection, music activities may increase the quality of long-term relationships by creating intimacy between partners (see Kreutz and Feldhaus, 2023 ). Moreover, a broader spectrum of mate cues needs to be studied to get a better understanding of the relative importance of music-related cues, as well as other cues of human artisticality ( Varella, 2021 ), creativity ( Kaufman et al, 2016 ; Novaes and Natividade, 2023 ) and humor ( Kaufman et al, 2008 ). Finally, future studies should account for cultural stereotypes related to musical styles ( Zillmann and Azra, 1989 ), and consider music preferences and different types of musical proficiency in their research designs ( Bongard et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, as long as they are all grounded in natural selection, distinct theories may be easier to subsume under an overarching theory ( Savage et al, 2021 ), but as soon as sexual and natural selection mechanisms both play a role, theory building becomes more challenging ( Keller et al, 2023 ). Another related challenge will be to develop explanatory theories that describe the specific evolutionary mechanisms involved in the emergence of musicality, along with their respective time-scales (see also Novaes and Natividade, 2023 ).…”
Section: Origins Of Musicalitymentioning
confidence: 99%
“…For instance, Miller (2008) suggested that many human behaviors, including music, are honest markers of general intelligence, and general fitness ( Miller, 2008 ). Creativity may indicate a well-functioning nervous system, which would have other survival benefits ( Watkins, 2017 ; Novaes and Natividade, 2023 ). If general creativity is a marker of fitness, then musical creativity may be likewise ( Miller, 2000 ).…”
Section: Evolutionary Biology Of Music and Lovementioning
confidence: 99%